ANALYSIS OF THE IMPACT OF MATERNAL AGE ON PREGNANCY (CIPEEX, 2025)
INTRODUCTION: Pregnancy at an advanced age, older 35 years old, has become an increasingly common reality today. Factors such as professional career, search for financial stability, advancement of assisted reproduction techniques and oocyte cryopreservation, contribute to the postponement of pregnancy. However, postponing this event can lead to negative biological and psychological consequences, which increases the chance of complications for the mother and baby. OBJECTIVE: To analyze the consequences of advanced maternal age in pregnancy. METHODOLOGY: An integrative review was carried out using the PICo strategy for data collection. The articles were found through descriptors present in the DECS, being applied in the following databases: Biblioteca Virtual em Saúde (BVS), PubMed and Scielo. In addition, the studies were selected based on specific inclusion and exclusion criteria and analyzed for their contribution to the response of the work objective. RESULTS: Initially, a study conducted with more than 27,000 pregnant women, classified into 3 groups according to age (< 35 years, 35-40 years and > 40 years), indicated an increased risk of gestational diabetes mellitus (GMD) and hypertensive disorders from 35 years. In addition, this research points out that pregnant women over 40 years old have greater chances of intensive care unity (ICU) hospitalization and postpartum hemorrhage. Regarding the impacts on the baby, research points to the higher risk of fetal death, neonatal hospitalization, premature birth, low birth weight, intrauterine growth restriction (IUGR) and genetic anomalies, mainly Down Syndrome. CONCLUSION: The analysis of the results allows us to conclude that there is a great impact of advanced maternal age on maternal-fetal health, with losses extending from the predisposition to the emergence of chronic diseases to fetal death.
Keywords: Fertility; Advanced MaternalAge; Obstetrics